Híbridos y líneas endocriadas de gusanos de seda (Lepidoptera: Bombyx mori L.): resultados productivos preliminares - Basso, C.P. (2014)
TIn Argentina sericulture is a new activity and is carried out by small producers as a complementary activity. The use of hybrid vigor in the silk production is used in several developed countries and the productivity and the quality depend on the hybrid involved. The objective of this work is to evaluate, in a preliminary way, some productive features of hybrids derived from inbred lines from the Faculty of Agronomy of the University of Buenos Aires. Were used four inbred and six crosses between them were bred in controlled conditions of temperature and humidity. Were fed four times a day with fresh mulberry leaves. In a 20 individuals sample four quantitative variables were measured: larval weight in the 5th stage, whole cocoon weight, cocoon without pupa weight and cocoon length. Significant differences between the means of the 10 genotypes for all the variables analyzed were detected. The crosses have shown different results depending on the crossing and the studied character. The overall result is that the hybrids productivity in these preliminary trials shows the superiority of some crosses over others and over the inbred lines.